The Effect of Nutmeg Seed (M. fragrans) Extracts Induces Apoptosis in Melanoma Maligna Cell’s (B16-F10) - Susianti Susianti; Ronny Lesmana; Supriatno Salam; Euis Julaeha; Yuni Susanti Pratiwi; Nova Sylviana; Hanna Goenawan; Ahmad Kurniawan; Unang Supratman (The Indonesian Biomedical Journal, 2021)
BACKGROUND: Nutmeg (Myristica fragrans H.), one of native plants of Maluku Indonesia, has long been used as traditional medicines especially to treat tumors, externally to treat skin infections. M. fragrans also has important biological activities as anticancer. However, antimelanoma activity of M. fragrans remains unknown. The aim of this study is to compare M. fragrans extracts as anticancer on melanoma B16-F10 cells by inducing apoptosis.METHODS: M. fragrans seed was extracted with ethanol then fractionated with n-hexane, ethyl acetate, and n-butanol. B16-F10 melanoma cells were cultured and treated with various doses and tested using resazurin reduction assay. Apoptosis signalling via caspase-3 was measured by using western blot.RESULTS: The extract and fractions of M. fragrans reduced viability of cells with IC50 value for ethanol extract 21.83 µg/mL, ethyl acetate fraction 21.66 µg/mL, n-hexane fraction 47.53 µg/mL, and n-butanol fraction >1,000 µg/mL. The active fraction of ethyl acetate induced apoptosis via caspase-3 proteins similar with cisplatin as positive control in B16-F10 cells at 10 hours treatment.CONCLUSION: Taken together, M. fragrans ethyl acetate fraction has the highest IC50 than n-hexane and n-butanol fractions that significantly inhibited B16-F10 cell proliferation by inducing apoptosis via caspase-3. It provides the insight that it has the most potential activity as a chemopreventive agent for addressing melanoma skin cancer.KEYWORDS: M. fragrans, apoptosis, fraction, melanoma